Biomimetic nanotherapeutics for targeted drug delivery to glioblastoma multiforme - Xin Yuan Lim; Sharah Mae Capinpin; Nagarjun Bolem; Aaron Song Chuan Foo; Wai‐Cheong George Yip; Alan Prem Kumar; Daniel Boon Loong Teh (Wiley, 2023)
Abstract Glioblastoma multiforme (GBM) is an aggressive brain tumor with poor prognosis and high mortality, with no curative treatment to date as limited trafficking across the blood-brain barrier (BBB) combined with tumor heterogeneity often leads to therapeutic failure. Although modern medicine poses a wide range of drugs that are otherwise efficacious in treating other tumors, they often do not achieve therapeutic concentrations in the brain, hence driving the need for more effective drug delivery strategies. Nanotechnology, an interdisciplinary field, has been gaining immense popularity in recent years for remarkable advancements such as nanoparticle (NP) drug carriers, which possess extraordinary versatility in modifying surface coatings to home in on target cells, including those beyond the BBB. In this review, we will be highlighting recent developments in biomimetic NPs in GBM therapy and how these allowed us to overcome the physiological and anatomical challenges that have long plagued GBM treatment.